2016
DOI: 10.1093/pasj/psw026
|View full text |Cite
|
Sign up to set email alerts
|

SXDF–ALMA 2-arcmin2 deep survey: 1.1-mm number counts

Abstract: We report 1.1 mm number counts revealed with the Atacama Large Millimeter/submillimeter Array (ALMA) in the Subaru/XMM-Newton Deep Survey Field (SXDF). The advent of ALMA enables us to reveal millimeter-wavelength number counts down to the faint end without source confusion. However, previous studies are based on the ensemble of serendipitously-detected sources in fields originally targeting different sources and could be biased due to the clustering of sources around the targets. We derive number counts in th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
43
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 39 publications
8
43
0
Order By: Relevance
“…We also show the counts using seven SMGs that do not have z spec =3.09. Previous ALMA results (Karim et al 2013;Ono et al 2014;Simpson et al 2015a;Fujimoto et al 2016;Hatsukade et al 2016;Oteo et al 2016) are also shown. The flux density of the counts are scaled to 1.1mm flux density, assuming a modified black body (similar with Figure 9; S 1.1mm /S 870μm = 0.56, S 1.1mm /S 1.2mm =1.29, S 1.1mm /S 1.3mm =1.48).…”
Section: Size Measurement and Star Formation Rate Surface Densitymentioning
confidence: 58%
See 2 more Smart Citations
“…We also show the counts using seven SMGs that do not have z spec =3.09. Previous ALMA results (Karim et al 2013;Ono et al 2014;Simpson et al 2015a;Fujimoto et al 2016;Hatsukade et al 2016;Oteo et al 2016) are also shown. The flux density of the counts are scaled to 1.1mm flux density, assuming a modified black body (similar with Figure 9; S 1.1mm /S 870μm = 0.56, S 1.1mm /S 1.2mm =1.29, S 1.1mm /S 1.3mm =1.48).…”
Section: Size Measurement and Star Formation Rate Surface Densitymentioning
confidence: 58%
“…We briefly describe the method below (for more detail, see Hatsukade et al 2016). Model sources created by scaling the synthesized beam are injected into the image map corrected for primary beam attenuation.…”
Section: Completeness and Flux Boostingmentioning
confidence: 99%
See 1 more Smart Citation
“…Its significantly higher angular resolution compared to single-dish telescopes (<  3 ) and the unparalleled sensitivity allow us to reach flux density levels in (sub)millimeter continuum maps even deeper than those achieved by studies of galaxy cluster fields or based on stacking analysis. Several recent studies have individually pinpointed (sub)millimeter sources down to 0.1 mJy in the 1 mm band (Hatsukade et al 2013;Ono et al 2014;Carniani et al 2015;Oteo et al 2016;Dunlop et al 2016;Hatsukade et al 2016). Some of these surveys have used clever approaches by taking advantage of archival data (Ono et al 2014;Carniani et al 2015;Fujimoto et al 2016), including ALMA calibration fields (Oteo et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The number density of the brightest SMGs with apparent submm flux in excess of 10 mJy at 850µm is ∼ 5 deg −2 (Hatsukade et al 2016), and the intrinsic Star Formation Rate (SFR) can exceed 1000 M ⊙ yr −1 if the submillimeter flux arises entirely from star formation. Although they are rare, these SMGs host the most intense starbursts in the entire universe and may represent the formation sites of massive elliptical galaxies.…”
Section: Introductionmentioning
confidence: 99%